2020
DOI: 10.1016/j.jnoncrysol.2019.119727
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mixed La-Y doping on water resistance of phosphate glass

Abstract: In this work, the effect of mixed La-Y doping on the water resistance of (x=0, 4, 8, 12, 16 mol%) glasses was studied.The glass structure, glass transition temperature (T g ), dc conductivity (σ dc ) and water resistance of glass were respectively characterized by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimeter (DSC), electrochemical workstation and water resistance test. The results show that with the gradual replacement of Y 2 O 3 by La 2 O 3 , the value of Q (2) (Q 2 conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The conductivity was measured by HIOKI 3522-50lCR testing instrument (HIOKI, Kagoshima, Japan) with experimental test frequency range and the test temperature of 0–100 kHz and 237 °C, respectively. The chemical durability [ 27 , 28 ] was tested by placing bulk samples polished on six sides in a test tube containing 100 mL of high-purity deionized water. After heating in a 90 °C water bath for 48 h, the glass dissolution rate (D r ) and the ionic release concentrations of each ion in the test tube were measured.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…The conductivity was measured by HIOKI 3522-50lCR testing instrument (HIOKI, Kagoshima, Japan) with experimental test frequency range and the test temperature of 0–100 kHz and 237 °C, respectively. The chemical durability [ 27 , 28 ] was tested by placing bulk samples polished on six sides in a test tube containing 100 mL of high-purity deionized water. After heating in a 90 °C water bath for 48 h, the glass dissolution rate (D r ) and the ionic release concentrations of each ion in the test tube were measured.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…Suryanarayanan et al [ 19 ] studied the influence of trimethylamine on the anodic behavior of Ni, Cu, and Ni‐Cu alloys exposed to fluoride media indicating that the anodic dissolution and film precipitation of these metals can be explained through the LPRM. Li et al [ 20 ] reported that the Fe 78 Si 9 B 13 metallic glass alloys exposed to a saline environment show that the formation of insoluble products on the metallic surface is under ohmic control. Chauque et al [ 21 ] studied the formation of lithium titanate for application as anodes in lithium‐ion batteries showing the linear variation of current and potential with the scan rate which indicates the formation of resistive films on the electrode surface.…”
Section: Introductionmentioning
confidence: 99%